Platelet Satellitism: Ethylenediaminetetraacetic Acid Sample versus Heparin Sample - Atul Kumar Agarwal; Dinesh Agarwal; Manoj K. Deori (Assam Journal of Internal Medicine)
Platelet satellitism is a rare in vitro phenomenon presenting with platelets rosetting around neutrophils observed in peripheral blood smears prepared from blood samples anticoagulated with ethylenediaminetetraacetic acid (EDTA) but not with heparin sample. The subject was a 65-year-old woman presenting with pain abdomen at our hospital. As a routine investigation, complete blood count (CBC) was advised, and collection was done in EDTA vial. The sample was run in Sysmex Xs800i five-part hematology cell counter. The results of CBC were as follows: total leucocyte count: 15.59 × 103/uL; red blood cell count: 4.61 × 106/uL; hemoglobin: 12.8 g/dL; packed cell volume: 39.5%; mean corpuscular volume: 85.7fl; mean corpuscular hemoglobin (MCH): 27.8 pg; MCH concentration: 32.4 g/dL; and platelet: 26 × 103/uL. On preparation of blood smear and after staining with Leishman stain, the smear showed the formation of platelet rosette around the neutrophils. Platelet satellitism is, hence, defined as the formation of platelet rosetting or clumping around the neutrophils in sample collected in EDTA. Microscopic examination of samples collected in EDTA vial is important before commenting on platelet count.